2006
DOI: 10.1007/s10347-005-0032-2
|View full text |Cite
|
Sign up to set email alerts
|

Petrography and biosedimentology of the Rosso Ammonitico Veronese (middle-upper Jurassic, north-eastern Italy)

Abstract: A petrographic and biosedimentological study of the Rosso Ammonitico Veronese from the Trento Plateau (north-eastern Italy) shows that diagenetic (neomorphism, recrystallization) and biological processes (microbial content and pigmentation) influenced the formation and alteration of the carbonate matrix. The subject of this article is the interaction of early diagenetic processes and an attempt to explain the different colors of the matrix (red, pink, grey). Nearly 200 samples derived from 14 sections (Callovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…Early Devonian in the Czech Republic (Mamet et al 1997), Late Devonian in Belgium and France (Préat et al 1999;Boulvain et al 2001;Mamet and Préat 2005), Carboniferous of Spain (Della Porta et al 2006), Jurassic in Italy Préat 2003, 2005;Préat et al 2006) and Spain (Mamet and Préat 2007) have all conWrmed these observations. By no means is this to deny that abiotic detrital iron can also form red limestones as we have observed in the French Jurassic Prétry Limestone near Tournus, or Sampans Limestone near Dole (Chauve 1975).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Early Devonian in the Czech Republic (Mamet et al 1997), Late Devonian in Belgium and France (Préat et al 1999;Boulvain et al 2001;Mamet and Préat 2005), Carboniferous of Spain (Della Porta et al 2006), Jurassic in Italy Préat 2003, 2005;Préat et al 2006) and Spain (Mamet and Préat 2007) have all conWrmed these observations. By no means is this to deny that abiotic detrital iron can also form red limestones as we have observed in the French Jurassic Prétry Limestone near Tournus, or Sampans Limestone near Dole (Chauve 1975).…”
Section: Introductionsupporting
confidence: 54%
“…Oxygen and iron concentrations are relatively low; for instance, the red Italian Ammonitico Rosso present small iron contents (generally <350 ppm of Fe in the carbonates, Préat et al 2006) and since free O 2 is linked to Fe at the time of sedimentation, it is also limited. It is the remarkably small size of the hematite crystals, mostly inferior to the original carbonate micrite crystals, that Wnally explains the distribution and spread of the red pigmentation .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously studied the role of iron microfossils in the red pigmentation of the original Rosso Ammonitico from the Trento area, in the classical area of Altopiano di Asiago (Rosso Ammonitico Veronese, Mamet and Préat, 2003;Préat et al, 2006). However the Rosso Ammonitico term seems to have been used to describe different facies types and a controversy (Elmi, 1981) arose in the interpretation of the bathymetry (deep water bathyal versus cratonic shallow water).…”
Section: Introductionmentioning
confidence: 96%
“…In this context iron and manganese precipitated as oxides in the marginal areas where the contact with oxygenated water masses provided the necessary redox conditions. We have reported that dysoxic conditions allowing the precipitation of Fe oxy-hydroxides led to the red pigmentation of the micritic matrix in the RAV (Préat et al, 2006) and in numerous other red Phanerozoic limestones (Mamet and Préat, 2006a). Due to the particular sedimentary dynamics along an escarpment a major goal of this paper is to assess potential mechanisms that resulted in the iron and manganese formations.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation